Highly photoluminescent copper carbene complexes based on prompt rather than delayed fluorescence. Issue 38 (18th April 2016) - Romanov, Alexander S.; Di, Dawei; Yang, Le; Fernandez-Cestau, Julio; Becker, Ciaran R.; James, Charlotte E.; Zhu, Bonan; Linnolahti, Mikko; Credgington, Dan; Bochmann, Manfred
Abstract : Simple carbene complexes of copper halides give photoluminescence quantum yields of up to 96%, with sub-nanosecond emission lifetimes. Abstract : Linear two-coordinate copper complexes of cyclic (alkyl)(amino)carbenes (CAAC)CuX (X = halide) show photoluminescence with solid-state quantum yields of up to 96%; in contrast to previously reported Cu photoemitters the emission is independent of temperature over the range T = 4–300 K and occurs very efficiently by prompt rather than delayed fluorescence, with lifetimes in the sub-nanosecond range.